Instrumento multicritério de análise para a implantação de zonas industriais: variáveis legais, antrópicas e naturais - Ávila, Leandro Bittencourt (Universidade do Vale do Rio dos Sinos, 2018)
Currently, it is perceived that a choice of areas suitable for the implantation of industrial zones emphasizes the existing infrastructure, which impact is an economic view considering only the proximity of urban centers, the profit maximization and the cost reduction. However, the analysis and selection process of such areas is incomplete and imprecise, because there is no previous study that considers the valid legal variables and the physical and biotic characteristics of the environment (potentials and fragilities) in the urban territorial planning. Also, developing countries face environmental problems resulting from the intense and disorderly occupation of the territory through the urbanization process. Environmental problems and disordered occupation of spaces generate conflicts of land use between industry, government and society. This process causes environmental degradation of urban space and affects the quality of life of society. The present study aims to evaluate the variables for the definition of areas suitable for the installation of industrial zones in Viamão city, based on the developing of a specific methodology to the study proposal. The proposed method consists of analyzing the variables extracted from secondary data existing in the Environmental and Economic Zoning of Viamão city (in Portuguese: Zoneamento Ambiental e Economico – ZAE) and its products (hydrology, permanent preservation areas, conservation units, geology, pedology, highways, population density, thalweg, declivity, etc.), current legislation, bibliography on urban planning and variables studied through GIS. From the proposed methodology, the map algebra was applied to the spatialized variables that resulted in the final product called the Multicriteria Zone of Sustainable Industrial Allocation (in Portuguese: Zona Multicritério de Alocação Industrial Sustentável – ZMAIS). In addition, the ZMAIS was intergrated with the main state highways, the water network, the population density, the master plan and the macrozones of the ZAE. The activities, the ventures and their possible environmental impacts on water and soil quality were defined in the bordering of Viamão city. It has been verified that GIS is an efficient but only complementary urban planning tool that needs to be added to other planning instruments (master plan, sanitation, waste, urban mobility and urban afforestation plans, etc.) and the environmental and urbanistic rules of urban and rural space. The spatial information and analyze of the territory provides the managers and experts of urban and environmental planning with a broad view of the territory and helps the evaluation and release of licenses. Finally, the definition of the variables, the overlaps followed by map algebra, the criteria and weights described in the method of territorial analysis may be replicated in any region, as long as they respect the characteristics of each locality, and may also help in the production of new studies assisting in the spatial interpretation of the city.
Keywords: Zona industrial; Planejamento territorial urbano; Sistema de informação geográfica; Análise ambiental; Industral Zone; Urban planning; Geographic information system; Environmental analysis; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo